Teneurin Structure: Splice Variants of a Bacterial Toxin Homolog Specifies Synaptic Connections - Araç, Demet; Li, Jingxian (Frontiers in Neuroscience, 2019)
Teneurins are a conserved family of cell adhesion proteins that mediate cellular communication and play critical roles in embryonic and neural development. Their mechanisms of action remained poorly understood due in part to their unknown structures. In the recent years, three-dimensional structures of teneurins have been reported at atomic resolutions and revealed a clear homology to bacterial Tc toxins and no similarity to other eukaryotic protein. Another big surprise was the observation that alternatively spliced variants of teneurins interact with distinct ligands, and thus specifies excitatory vs. inhibitory synapses. In this review, we discuss TEN structure which, together with structure-guided biochemical and functional analyses, provide hints for the mechanisms of trans-cellular communication at the synapse and other cell-cell contact sites.